Penatalaksanaan Kegiatan Supervisi Kelas Sebagai Upaya Peningkatan Profesionalisme Guru Dalam Kegiatan Belajar Mengajar Di MTsN 3 Aceh Barat - Almunawar Khalil (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: The main issue of the implementation of this research was the low professionalism of teachers in teaching which was caused by: (1) the lack of opportunities for teachers to participate in training, both regionally and nationally; (2) less effective Teacher Working Group (KKG); and (3) educational supervision aimed at improving the learning process tends to focus on administrative aspects. The research was conducted by teachers at MTsN 3 Aceh Barat for the 2018 academic year starting from July to December, for 6 (six) months. The research subjects were 6 teachers, while the object of the research was the professionalism of teachers in implementing learning. The data was obtained by doing an observation and documentation. The results showed that the professionalism of teachers in planning the lessons at MTsN 3 Aceh Barat was in a good category. This can be proven by the results of the learning planning in the first cycle reaching an average of 71.35 which is included in the good category, then in the second cycle it reaches an average of 83.70 which is included in the good category. Thus, there was an increase in the implementation of learning by 12.35% and so does the improvement of learning abilities. The increase in the ability of the teacher can be proven from the results of the pre-learning cycle prediction showing an average of 68.82 and in the first cycle it increased by 11.96% with an average of 80.78, then in the second cycle it increased again by 10.38%, and reached 91.17 that is in very good category. Increasing the ability of teachers in learning planning as well as the implementation of learning activity in cycle I reached a value of 71.35, and 83,70 in cycle II. It means that there was an improvement about 12.35%.. Abstrak: Permasalahan yang menjadi dasar dari pelaksanaan kegiatan penelitian ini adalah rendahnya profesionalisme guru dalam mengajar yang diakibatkan oleh: (1) kurangnya kesempatan guru mengikuti pelatihan, baik secara regional maupun nasional; (2) kurang efektifnya Kelompok Kerja Guru (KKG); dan (3) supervisi pendidikan yang bertujuan memperbaiki proses pembelajaran cenderung menitikberatkan pada aspek administrasi. Penelitian dilakukan pada guru di MTsN 3 Aceh Barat Tahun Pelajaran 2018 yang dimulai bulan Juli sampai Desember, selama 6 (enam) bulan. Subjek penelitian sebanyak 6 orang guru, adapun objek penelitiannya adalah adalah profesionalisme guru dalam melaksanakan pembelajaran. Teknik pengumpulan data dengan kegiatan observasi dan dokumentasi. Hasil penelitian menunjukkan Profesionalisme guru dalam perencanaan pembelajaran di MTsN 3 Aceh Barat dalam kategori baik. Hal ini dapat dibuktikan dengan melalui hasil penilaian perencanaan pembelajaran pada siklus I mencapai nilai rata-rata 71,35 termasuk dalam kategori baik, kemudian pada siklus II mencapai nilai rata-rata 83,70 termasuk dalam kategori baik. Dengan demikian terjadi peningkatan pelaksanaan pembelajaran sebesar 12,35%. Sedangkan peningkatan kemampuan melaksanakan pembelajaran. Peningkatan kemampuan guru tersebut dapat dibuktikan dari hasil penilaian pra pembelajaran pra siklus menunjukkan rata-rata 68,82 dan pada siklus I meningkat sebesar 11,96 % dengan nilai rata-rata 80,78, kemudian pada siklus II meningkat lagi sebesar 10,38 % menjadi 91,17 dengan kategori sangat baik. Peningkatan kemampuan guru dalam pra pembelajaran/perencanaan pembelajaran tersebut sekaligus diikuti dengan peningkatan kemampuan guru dalam melaksanakan pembelajaran pada siklus I mencapai nilai sebesar 71,35 dan pada siklus II mencapai nilai rata-rata sebesar 83,70, maka terjadi peningkatan sebesar 12,35 %.